The aroma peculiaritiesof some white wines from autochthonous grapes varieties from western europe and Ukraine - Ткаченко, Оксана Борисовна; Тринкаль, Ольга Валентиновна (Eastern-European Journal of Enterprise Technologies, 2015)
The paper considers significance of using local grapes varieties in manufacturing local wines that are important for enotourism. We have researched white dry wines from autochthonous grapes varieties from Western Europe and Ukraine that are presented on the Ukrainian wine market. We have submitted statistical data оn propagation of aboriginal grapes varieties in Western Europe and Ukraine from 2000 to 2010. Autochthonous grapes varieties are a valuable genetic heritage owing to their productivity and biological resistance as tokens of authenticity and specificity. The major criterion in characterizing the researched wines was aromatic complex, since it is largely predetermined by the grapes variety. We have researched an aromatic complex of wines from autochthonous grapes varieties from Spain (Albarino, Verdejo, and Garnacha Blanca), Italy (Vermentino, Garganega, Grillo, and Cortese), Greece (Moskhofilero andAssirtiko), and Ukraine (Kokur white andTeltiKuruk); the sensor analysis of wines was made under ISO international standards. The obtained data have laid the basis for organoleptic profiles; we have determined and assessed major descriptors of the researched winesdepending on their intensity. During the research of wines from European aboriginal varieties, we outlined distinctive features and peculiarities of the aromas and proved the expedience of using autochthonous grapes varieties in manufacturing modern local wines.